Regional Economic Outlook, May 2009, Europe : Addressing the Crisis. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2009)
Europe is in a deep recession. Adverse feedback between the financial and real sectors and across borders is likely to delay the recovery and create downside risks. Unprecedented policies have been undertaken to address the crisis-but are they likely to be successful and sufficiently coordinated for a tightly integrated region? To restore trust and confidence in financial markets, additional and forceful action will be essential. Maintaining fiscal support should help soften the downturn, in particular if sustainability is supported by solid medium-term strategies and fiscal frameworks. To be effective, these policies require coordination across advanced and emerging economies. The report's analytical work underpins the link between fiscal sustainability, coordination, and effectiveness, and stresses that emerging markets have been affected differently by the crisis, with the quality of policies and external vulnerabilities being key factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet